SCIENTIFIC JUSTIFICATION OF MEASURES TO ENSURE SAFE WORKING CONDITIONS FOR EMPLOYEES ENGAGED IN MODERN ALUMINUM PROFILE PRODUCTION - Tashpulatova Munisa Nigmanzhanovna; Safarov Mirzokhid Boltaevich; Samigova Nargiz Raimovna (Bright Mind Publishing, 2025)
Based on the conducted research, a set of preventive measures has been developed to optimize working conditions and preserve the health of workers engaged in modern aluminum profile production.
Keywords: Occupational hygiene, industrial risk assessment, artificial intelligence in public health, harmful production factors.